Effect of processing on the total phenolic content and antioxidant capacity of yacon (Smallanthus sonchifolius) - Lucas, Jenny Lyn C. (College of Home Economics, University of the Philippines Diliman, 2011)
ABSTRACT The aim of this study is to determine the effect of boiling, steaming and powder making on the total phenolic content and antioxidant activity of yacon (Smallanthus sonchifolius) tubers extracted with methanol. Results were all compared to untreated (control) yacon tuber. Using the Folin-Ciocalteu assay, the total phenolic content of methanolic yacon tuber extracts was determined. Antioxidant properties such as antiradical activity to 2-2-diphenyl-1-picrylhydrazyl (DPPH) radical, reducing power and total antioxidant activity using the ferric thiocyanate assay were evaluated. The total phenolic content of yacon tubers ranged from 231.1 to 433.6 mg GAE/100g dry weight. Yacon tubers processed into powder have significantly retained much of the total phenolic content while the control had the least total phenolics; boiled yacon tubers showed no significant effect in the retention of the total phenolic content. Steaming of yacon tubers showed considerable antiradical activity to DPPH and reducing power as the effective concentration (EC50) obtained from both measures were the lowest among all treatments, 6.21 and 29.48 mg/ml respectively. Boiled and powdered yacon tubers, with EC50 values of 8.12 and 8.29 mg/ml respectively, did not have significant effect on the antiradical activity to DPPH; contrary, both processing techniques have considerable effect on the reducing power although lower to that of the steamed yacon tubers. Total antioxidant activity of yacon tubers ranged from 78.86 to 88.42%. No significant difference was detected across all treatments. Although low in its negative correlation (R^2 = 0.201; r=-0.448), only the reducing power can be attributed to the total phenolic content of yacon tubers (P=0.028); indicating better reducing power with increasing phenolic concentration. On the other hand, total antioxidant activity of yacon tubers may not be attributed only to its antiradical activity and reducing power with low (R^2 < 0.7) and insignificant correlation (P>0.05) to both measures. Results obtained in the study showed that yacon tubers are best consumed when steamed or processed into powder to maximize its antioxidant benefits.